PENGEMBANGAN KOMIK BERBASIS PENDIDIKAN LINGKUNGAN HIDUP UNTUK MENINGKATKAN KEMAMPUAN LITERASI PADA SISWA KELAS III SDN 59 RASALEWI KOTA BIMA - Nurhidayaturrahman; Akbar, Muh. Rijalul; Widayati, Ulfa; Leha, Noor; Syakir, Akhmad; Hamidah, Jamiatul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to determine (1) the feasibility of environmental education-based comics as a medium to improve literacy among third-grade elementary students, (2) the practicality of using the comics in the learning process, and (3) the effectiveness of the comics in enhancing students’ literacy skills. This study used a Research and Development (R&D) design involving media experts, material experts, and third-grade students of SDN 59 Rasalewi Kota Bima. Data were collected through questionnaires, observations, tests, and documentation in both qualitative and quantitative forms. The developed comic focused on the theme of environmental education within Indonesian language lessons. The results showed that the comic met the criteria for a valid learning media. Media validation increased from 87.5% to 92.5%, and material validation rose from 78.3% to 80%, meeting the feasibility standards based on Sugiyono’s criteria. Student responses were very positive with a score of 97%, and the practicality score from classroom observations was 79.2%. Effectiveness testing showed an improvement in average literacy scores from 63% (pre-test) to 86% (post-test), with an N-gain score of 0.62 categorized as moderate. These results indicate that the environmental education-based comic is very feasible, practical, and moderately effective for improving literacy skills in third-grade students.